Assessing the Tolerance of Sagittaria Lancifolia (Spear Plant) to Linear Alkylbenzene Sulfonates (LAS) Exposure - Salsa Nabila; Risa Purnamasari; Eva Agustina; Rony Irawanto (Indonesian Journal of Biology Education, 2023)
One of pollutant that commonly found in aquatic environment is detergent. Detergent pollution can cause skin irritation and other health problems in humans and animals that use contaminated water sources. To address this issue, it is critical to implement effective policies and regulations to control detergent pollution and promote sustainable wastewater management practices in Indonesia. One of the approaches to overcome detergent pollution is to use plants as pollutant absorbing agents, or commonly called phytoremediation techniques. Therefore, this study aims to determine the growth response of spear plant (Sagittaria lancifolia) in response to the stress of Linear Alkylbenzene Sulfonate (LAS) detergent. This research is an experimental research using a completely randomized design (CRD). There were four treatments tested with three replicates for each treatment. Treatment variations were based on the concentrations used in this study, namely 0 mg/L, 10 mg/L, 30 mg/L, and 50 mg/L. The research was conducted for four months, starting from July to October 2022, and was conducted in the greenhouse of Purwodadi Botanical Garden – BRIN. The result showed that although it experienced some morphological changes such as leaf drying, discoloration, and structural changes, Sagittaria lancifolia were able to survive and conduct metabolic activities properly during 28 days of Linear Alkylbenzene Sulfonates (LAS) pollutant stress.  Thus, Sagittaria lancifolia are able to be used as one of the strategies in restoring the aquatic environment polluted by domestic waste, including LAS detergent.